Effect of body condition score on reproductive performance of crossbred dairy cows in the Tanga region, Tanzania - Samson Jonass Goodluck; Athuman Shaban Nguluma; Sebastian Wilson Chenyambuga; Zabron Cuthibert Nziku; Sizya Lugeye; Mwemezi Lutakyawa kabululu; Padraig French (Ovozoa: Journal of Animal Reproduction, 2025)
First service conception rate (FSCR) is a key determinant of reproductive efficiency and farm profitability in dairy cattle. Failure to conceive leads to increase the number of services per conception (NSC), breeding costs, calving intervals, and delays in replacement heifers. Body condition score (BCS) which reflects energy reserves, plays a critical role in reproductive efficiency. However, limited data exist on this relationship in Tanzania. This study evaluated the association between BCS, FSCR, and NSC in 86 crossbred dairy cows reared at TALIRI and LITA farms in Tanga from May to August 2024. Cows were synchronized using two PGF2α injections, followed by estrus detection and insemination protocol. BCS was scored at insemination. Cows returning to estrus (RE) were re-inseminated. Pregnancy was confirmed 90±3 days post-insemination. Data on BCS, FSCR, NSC, and RE were analyzed using chi-square test, logistic regression and GLM in SAS 9.4. Mean BCS, NSC and FSCR were 2.91±0.38, 1.28±0.60 and 54.65%, respectively. BCS significantly influenced FSCR (χ²= 42.66, p <0.0001). Cows with moderate BCS (2.6-3.4) had an 89.0% likelihood of conceiving at first service, lower NSC (1.13±0.18), and fewer RE (1.10 ± 0.14 per cow), compared to cows with low or high BCS. Cows with low and high BCS did not significantly differ (p= 0.9132) in FSCR, NSC and RE. Interaction between BCS 2.6-3.4 and parity group 2 was observed significant on FSCR (χ²= 22.59, p <0.0001). These findings suggest that maintaining a moderate BCS optimizes fertility in crossbred dairy cows.